2014
DOI: 10.3844/ajessp.2014.289.300
|View full text |Cite
|
Sign up to set email alerts
|

Gold Mining in Igun Ijesha, Southwest Nigeria: Impacts and Implications for Water Quality

Abstract: This study was carried out in Igun-Ijesha, Osun State, Nigeria to determine the likely hotspots of water contamination for future treatment trials. Water quality analyses were based on physico-chemical and heavy metal parameters of surface and ground water collected from the study community. A total of thirty-eight water samples were collected between September 2012 and February 2013 and analyzed using standard procedures. Concentrations of heavy metals were determined using Atomic Absorption Spectrophotometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…33 The high TDS value recorded during the study period might be due to runoff from the mining grounds to the reservoir as well as runoffs from farmlands. 4,30 Nmerukini et al 34 reported that high total dissolved solids could be due to the release of carbonates, bicarbonates, chlorides, phosphates, nitrates, calcium, magnesium, sodium, potassium, manganese, and organic matter. The high organic matter concentration observed during the period of study was within the range of 2.67 -15.15 mg/L (8.84 ± 4.40 mg/L).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The high TDS value recorded during the study period might be due to runoff from the mining grounds to the reservoir as well as runoffs from farmlands. 4,30 Nmerukini et al 34 reported that high total dissolved solids could be due to the release of carbonates, bicarbonates, chlorides, phosphates, nitrates, calcium, magnesium, sodium, potassium, manganese, and organic matter. The high organic matter concentration observed during the period of study was within the range of 2.67 -15.15 mg/L (8.84 ± 4.40 mg/L).…”
Section: Discussionmentioning
confidence: 99%
“…3 However, mining activities may also have negative impacts on the environment due to exploration or/ mining process, inappropriate and wasteful working practices, and use of chemicals like mercury and cyanide in mining activities has been responsible for different types of adverse effects on the physical environment such as ecological disturbance, biodiversity loss, pollution of air, land, soil, water as well as the flora and fauna, landscape degradation and radiation hazards to man. 4 The potential adverse impacts of mining have also been asserted to include displacement of local people from ancestral lands, marginalization, and oppression of people belonging to lower economic classes. 5 Cyanide is one of the few poisons chemicals that it antidotes exist if inhaled or injected by any organisms which can cause a dramatic and severe poisoning that can quickly result in death.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, arsenic has been detected in drinking water sources (both surface water and groundwater) above acceptable levels of 0.01mg/l in the Northern region with a concentration of 0.02 to 0.80mg/l [2]. Such Northern regions with high arsenic contamination include Biu Volcanic North-Eastern Province of Nigeria [16], Kano [17], Zaria and environs [18], Kaduna [3,4], Borno [19], and Sokoto [20] and also, it has been detected in high concentration in some places in south western Nigeria, such places include Osun and Ogun States [21][22][23]. Although, arsenic contamination is not too severe in the south-south region of Nigeria, however some levels have been detected in some areas and it's below the permissible limit of 0.01mg/l [2] for drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals have the ability to persist in natural ecosystems for an extended period (Nomanbhay and Palanisamy, 2005; Berar and el., 2011). Recent, environmental pollution has increasingly gained a global interest (Ayantobo and al., 2014). The main source of contamination of the environment is industry, the mining activities that pollute the environment are: extraction and preparation, which contributes to emissaries polluted with toxic substances (Cosma, 2012).…”
Section: Introductionmentioning
confidence: 99%